Understanding changes in doctor moral hazard behaviour in response to government healthcare reform - Wang, Yaohui; He, Lina; Liu, Quanlong; Li, Xinchun (Acta Bioethica, 2020)
Doctor moral hazard has a significant effect on the doctor-patient relationship, increases the cost of healthcare, and introduces medical risks. It is a global concern. Doctor moral hazard behaviour is evolving in response to China’s healthcare reform program which was inaugurated in 2009.A scientific understanding of doctor behaviour would facilitate the prevention and control of doctor moral hazard behaviour. This study used the principles and methodology of Glaser and Strauss’s grounded theory. Theoretical and snowball samplings were used to identify 60 subjects. Semi-structured in-depth interviews were conducted with each subject. Themes were identified through substantial (open) coding and theoretical coding. Six types of doctor moral hazard behaviour were extracted from the data. A behavioural model was described and diagrammed to provide a conceptual framework of current doctor moral hazard behaviour. The conceptual model of doctor moral hazard behaviour can be used in several ways to correct or prevent undesirable actions. Rules governing hospital procedures can be strengthened and enforced by supervision and punishment; the asymmetry of information between doctor and patient can be reduced; patient participation in treatment decisions can be increased; the effectiveness of medical ethics education can be improved.